THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE, BEHAVIOR, AND NUTRITIONAL STATUS WITH THE INCIDENCE OF ANEMIA IN ADOLESCENT GIRLS - Rosani Naim; Rosmiati, Rosmiati; Ekawati Saputri (Nusantara Hasana Journal, 2025)
Anemia is a common nutritional problem among adolescent girls, primarily due to iron deficiency, which can affect physical growth, academic performance, and daily productivity. This study aimed to examine the relationship between knowledge, attitude, behavior, and nutritional status with the incidence of anemia among adolescent girls at Madrasah Tsanawiyah Nurul Iman Pomalaa. A cross-sectional study was conducted with 146 female students selected through purposive sampling. Data collection included questionnaires, anthropometric measurements for Body Mass Index (BMI), and hemoglobin (Hb) level testing. The results showed no statistically significant associations between knowledge (p = 0.756), attitude (p = 1.000), behavior (p = 0.246), and nutritional status (p = 0.493) with anemia incidence. However, all odds ratios were greater than 1, suggesting a descriptive tendency toward increased anemia risk among participants with poor knowledge, negative attitudes, unhealthy behaviors, or abnormal nutritional status. These findings emphasize the importance of preventive efforts through school- and family-based health education, especially regarding iron-rich dietary intake and compliance with iron supplementation. Further research is recommended to include other contributing factors such as menstruation patterns, psychological stress, and physical activity to better understand the multifactorial nature of anemia in adolescents.